Clinically approved treatments for refractory glaucoma - Т.А. Zhigalskaya; O.I. Krivosheina (РМЖ "Клиническая офтальмология")
The article presents the historical development of surgical techniques for refractory glaucoma. This issue is one of the most disputable and difficult ones in modern ophthalmology. Currently, glaucoma is medically and socially important disorder. More than 70 million patients suffer from glaucoma worldwide. Its incidence progressively increases thus resulting in the steady growth of disability. Refractory glaucoma has a significant role. Refractory glaucoma is defined as uncontrolled intraocular pressure (IOP) despite anti-glaucoma medications and surgeries. These are glaucoma in patients younger than 40, congenital and juvenile glaucoma, uncontrolled primary glaucoma after surgery which requires reoperation, and secondary glaucoma (e.g., uveitic, traumatic, neovascular etc.). Currently, cyclodestructive procedures, intraoperative applications of antimetabolites, and glaucoma drainage device implantation are used to manage refractoty glaucoma. However, despite wide choice of surgical techniques for refractory glaucoma, stable IOP-lowering effect after glaucoma surgery remains elusive.  Keywords: refractory glaucoma, decompensation, intraocular pressure, regeneration, scarring, surgery.  For citation: Zhigalskaya Т.А., Krivosheina О.I. Clinically approved treatments for refractory glaucoma. Russian Journal of Clinical Ophthalmology. 2019;19(2):110–115.  About the authors: Tatiana A. Zhigalskaya — graduate student of the Department of Ophthalmology, ORCID iD 0000-0003-3110-4112; Olga I. Krivosheina — MD, PhD, Professor, Head of the Department of Ophthalmology, ORCID iD 0000-0001-7509-5858. Siberian State Medical University. 2, Moscow tract, Tomsk, 634050, Russian Federation. Contact information: Tatiana A. Zhigalskaya, e-mail: 7atyana@gmail.com. Financial Disclosure: no authors have a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 18.09.2018.